2001
DOI: 10.1103/physrevb.63.113404
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of the Ag(111) surface measured by x-ray scattering

Abstract: We have investigated the structure of the Ag͑111͒ surface, for temperatures between 300 and 1100 K ͑90% of the bulk melting point͒, using synchrotron x-ray diffraction. Our data show no evidence of the anomalously large surface thermal expansion previously reported by medium-energy ion-scattering ͓Phys. Rev. Lett. 72, 3574 ͑1994͔͒. At all temperatures we find that the interlayer separations at the surface differ from their bulk counterparts by less than 1%, indicating that the surface expands similarly to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Interestingly, for Ni͑111͒, our calculation and the MEIS data 13 show full agreement up to 0.64T m . Recent experiments using x-ray diffraction 43 for the case of Ag͑111͒ is in full agreement with our predictions.…”
Section: Interlayer Separationsupporting
confidence: 79%
“…Interestingly, for Ni͑111͒, our calculation and the MEIS data 13 show full agreement up to 0.64T m . Recent experiments using x-ray diffraction 43 for the case of Ag͑111͒ is in full agreement with our predictions.…”
Section: Interlayer Separationsupporting
confidence: 79%
“…The four-layer slab model employed here (two bottom layers fixed) gives the correct relaxation sign and magnitude for the change of the first (Dd 12 /d b = À0.9%) and the second interlayer spacing (Dd 23 /d b = À0.3%) relative to the bulk spacing (d b ), when compared to LEED 62 and X-ray scattering studies. 63 Note that the LEED study showed that the third interlayer spacing is the same as the bulk interlayer spacing thus legitimating our four-layer slab approach. More refined results would need the consideration of finitetemperature effects which have been discussed in the past but are not the aim of this study.…”
Section: Methodsmentioning
confidence: 79%
“…12 This type of analysis has been extensively used in our previous studies of metal homoepitaxy. 10,12 At 100 K, however, the reflectivity profiles measured around the Bragg reflection exhibit two new features: a pronounced asymmetry and interference fringes with a periodicity corresponding to the film thickness. Both features are well explained by a model 6 where, in addition to some surface roughness, a surface-normal compressive strain:…”
Section: mentioning
confidence: 99%